Design and Modeling of a Semiconductor Laser by Employing Silicon Carbide Polymers (6H-SiC, 3C-SiC and 4H-SiC) - Marjani, Saeid; Faez, Rahim; Marjani, Hamid (Asian Journal of Chemistry, 2012)
We present an edge emitting laser structure employing silicon carbide polymers only. In this structure, 3C-SiC well embedded in 6H-SiC barriers are used as the active region, which is sandwiched between the 6H-SiC mirror at the top and bottom of structure. The basic design goal is to use only silicon carbide polymers and decrease the threshold current and stable optical wavelength of the lasers with silicon carbide polymers. This paper provides key results of the device characteristics, including the light power versus electrical current and the optical wavelength versus current.